2021
DOI: 10.3390/diagnostics11020174
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of 18F–FDG–PET Parameters in Patients with Small Cell Lung Cancer: A Meta-Analysis and Review of Current Literature

Abstract: Many studies have suggested a prognostic value of one or several positron emission tomography (PET) parameters in patients with small cell lung cancer (SCLC). However, studies are often small, and there is a considerable interstudy disagreement about which PET parameters have a prognostic value. The objective of this study was to perform a review and meta-analysis to identify the most promising PET parameter for prognostication. PubMed®, Cochrane, and Embase® were searched for papers addressing the prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
(158 reference statements)
1
9
0
Order By: Relevance
“…Overall, six meta-analyses containing information on the prognostic value of PET with different radiopharmaceuticals in patients with NETs and NECs were included (Table 2) [8,12,17,20,27,41]. These evidence-based manuscripts provided quantitative data about the prognostic value of 68 Ga-SSA PET or 18 F-FDG PET in patients with thoracic and/or gastroenteropancreatic NETs [8,17,20] or SCLC [12,27,41] in terms of disease control rate (DCR), event-free survival (EFS), progression-free survival (PFS) or overall survival (OS).…”
Section: Prognostic Value Of Pet With Different Radiopharmaceuticals In Neuroendocrine Neoplasmmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, six meta-analyses containing information on the prognostic value of PET with different radiopharmaceuticals in patients with NETs and NECs were included (Table 2) [8,12,17,20,27,41]. These evidence-based manuscripts provided quantitative data about the prognostic value of 68 Ga-SSA PET or 18 F-FDG PET in patients with thoracic and/or gastroenteropancreatic NETs [8,17,20] or SCLC [12,27,41] in terms of disease control rate (DCR), event-free survival (EFS), progression-free survival (PFS) or overall survival (OS).…”
Section: Prognostic Value Of Pet With Different Radiopharmaceuticals In Neuroendocrine Neoplasmmentioning
confidence: 99%
“…Three different meta-analyses clearly demonstrated that 18 F-FDG PET has a significant prognostic value in patients with SCLC, in particular taking into account metabolic parameters at PET such as SUVmax of the primary lesion, metabolic tumor volume (MTV) or total lesion glycolysis (TLG) [12,27,41]. Higher values of these metabolic parameters were associated with a poorer prognosis regarding EFS, PFS and OS [12,27,41].…”
Section: Small Cell Lung Cancer (Sclc)mentioning
confidence: 99%
“…Changes in metabolic activity can be measured in vivo via metabolomics, magnetic resonance spectroscopy, PET, and stable isotope tracing [ 32 ]. In particular, 18-F-FDG PET-CT is not only used to diagnose malignant tumors of different cancers, but also reflects treatment response [ 33 ], while parameters such as SUV max , metabolic tumor volume, and total lesion glycolysis are associated with the prognosis of patients with cancer [ 10 , 11 , 12 , 13 , 14 , 34 ]. Previous findings suggest that the uptake of 18F-FDG has an independent prognostic value in patients newly diagnosed with NSCLC [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, higher [ 18 F]FDG uptake was associated with worse EFS and OS [ 69 ]. Furthermore, the association between higher values of [ 18 F]FDG quantitative parameters (such as [ 18 F]FDG SUVmax of the primary lesion, metabolic tumor volume, total lesion glycolysis) and inferior EFS, PFS, and OS was demonstrated [ 70 ].…”
Section: Imaging Of Nens With Radiolabeled Somatostatin Analoguesmentioning
confidence: 99%